Factors associated with fruits and vegetables among breast cancer patients in National Cancer Institute - Hamdan, Siti Nur Izzati; Abu Zaid, Zalina; Han, Ng Wai (Human Resource Management Academic Research Society, 2024)
Introduction: Fruits and vegetables (FV) contain bioactive components that can potentially improve breast cancer health outcomes. As significant number of breast cancer patients struggle to meet the World Health Organization's (WHO) recommendation consumption of at least ≥ 400 g/day of FV, this cross-sectional study aimed to investigate the factors associated with sociodemographic status, anthropometric measurement, biochemical data, medical characteristics, and stress level, with the consumption of FV among breast cancer patients at the National Cancer Institute, Putrajaya. Method: A total of 32 breast cancer outpatients were recruited using purposive sampling. Food Frequency Questionnaire (adapted from the Malaysian Adult Nutrition Survey) was used to assess FV consumption while Perceived Stress Scale was used to evaluate the participants' perceived stress levels. The inclusion criteria including all breast cancer outpatients, aged 18 years old and above, Malaysian and able to communicate verbally. Patients with chronic disease and fluid retention were excluded in this study. Results: The findings revealed that only 50% of the respondents managed to meet the WHO's recommended intake of FV. However, no significant associations observed between sociodemographic status, anthropometric measurement, biochemical data, medical characteristics, stress level, with the FV intake among the participants. Conclusion: The proportion of participants consuming an adequate amount remains relatively low. This is a concern that requires attention for future interventions by healthcare providers, especially dietitians, playing a crucial role in treatment efforts in the country and improve breast cancer outcomes.